Synthesis and docking studies of new 5-bromoindole-2-carboxylic acid oxadiazole derivatives as EGFR inhibitors - Hassan, Omeed Muhsin; Mahmood, Ammar A. Razzak; Tahtamouni, Lubna (Tikrit Journal of Pharmaceutical Sciences, 2023)
The current study reports the design and synthesis of novel oxadiazole derivatives of 5-bromoindole-2-carboxylic acid and their molecular docking properties. In order to determine the structure of the new oxadiazole derivatives (3, 4a, 4b), a number of spectroscopic techniques (IR and 1HNMR) were employed. Molecular docking analysis indicated that compounds 3, 4a, 4b showed favorable binding free energy against the EGFR tyrosine kinase domain. None of these compounds appeared to suppress cytochrome P450, and all of them showed appropriate absorption levels. Moreover, they did not exhibit any hepatotoxicity when tested in vitro. Compound 4a Reported to have the highest stability, with a good net binding energy, and an excellent binding energy with hot amino acids. Dipole moment is also rather high. This result is an indication of compound 4a is with superior capacity to create hydrogen bonds over erlotinib. Likewise, compound 4a was found to be the most stable in its interaction with EGFR tyrosine kinase. Finally, molecular dynamic simulation revealed excellent outcomes for compound 4a.